Refugee Characteristics as a Game-Changer for Integration in Fortress Europe - Osmandzikovic, Emina (European Scientific Journal, ESJ, 2019)
European security is an indispensable quality of its peace and democratic foundations. Failure to develop a coherent integration system has the potential to irreparably shake such foundations. This paper attempts to identify factors that influence integration and illuminate uncertainty around the refugee influx. Through a mixed-methods approach, I analyze secondary survey data of refugees across seven EU countries and conduct in-person interviews with key stakeholders. Survey analysis reveals that characteristics of being male and young positively shape refugees’ integration, a profile that highly resembles that of economic migrants. Topic modelling of interviews shows the fragmented image of refugee integration. Economically well-off EU states focus on legal aspects, whereas those not well-off focus on social integration. None of the two extremes are conducive to optimal integration in Europe. Overall, this paper depicts the importance of a mixed-methods approach to understanding the factors that influence refugee integration. The results are highly relevant, especially in the aftermath of the refugee crisis as an indispensable step safeguarding European security.